From Lovrin to Szécsény – remembrance to Béla Lipthay (1892-1974) - Bozsik, András (Acta Agraria Debreceniensis, 2011)
Béla Lipthay lepidopterologist, entomologist, museologist, agriculturist, hussar lieutenant, life-saving Roman Catholic, descendant of the historical family Lipthay de Kisfalud et Lubelle did a long way from his home village Lovrin to Szécsény, the one-time land of his ancestors. His life coincided with the disintegration of the historical Hungary, and the most serious trials of the Hungarian society, culture and spirit. These changes affected him as a member of Hungarian aristocracy many times and in fact wanted to destroy him. The fortune of the ancestors have been swept away by the storms of the wars, confiscated by the beneficiaries of tricky ideas of the new age and decimated by practical swindlers, but the human strength of character, the consciousness, the advantage of education and the with them associated ability, diligence, inventiveness and the sanctuary of faith have remained. All these made him possible to survive, to do his everyday hard creative work, which gained him the affection, the esteem and respect of the people living around him. Protecting his remembrance we evoke his many-sided, altruistic efforts for the Hungarian people and Hungary, and we can contribute to the creation of a better and just world.